Arctic Species Trend Index 2010: Tracking Trends in Arctic Wildlife - McRae, Louise; Zöckler, Christoph; Gill, Michael; Loh, Jonathan; Latham, Julia; Harrison, Nicola; Martin, Jenny; Collen, Ben (Conservation of Arctic Flora and Fauna (CAFF), 2010)
A 2010 analysis of the Arctic Species Trend Index (ASTI) dataset, an index used to track trend in Arctic fish, mammals and birds. In this report, vertebrate population-abundance data were used to produce an indicator of the trends in Arctic biodiversity over the past 34 years (1970 as the baseline1). This index tracks 965 populations of 306 species, representing 35% of all known vertebrate species found in the Arctic.